2003
DOI: 10.1210/en.2002-220013
|View full text |Cite
|
Sign up to set email alerts
|

Agouti-Related Protein Stimulates the Hypothalamic-Pituitary-Adrenal (HPA) Axis and Enhances the HPA Response to Interleukin-1 in the Primate

Abstract: alpha-MSH antagonizes many of the immune and neuroendocrine effects induced by inflammatory cytokines. Studies have shown that alpha-MSH attenuates the stimulatory effect of IL-1 on the hypothalamic-pituitary-adrenal (HPA) axis and plays a physiological role in limiting the HPA response to IL-1. Recently an alpha-MSH antagonist, agouti-related protein (AGRP), has been identified in the hypothalamus, which stimulates food intake by antagonizing the effects of alpha-MSH at specific melanocortin receptors. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…Also, AgRP stimulates ACTH and cortisol in female monkeys [39]. Consistent with previous findings [40], we observed that central administration of α-MSH reduces the increase in serum corticosterone levels induced by LPS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, AgRP stimulates ACTH and cortisol in female monkeys [39]. Consistent with previous findings [40], we observed that central administration of α-MSH reduces the increase in serum corticosterone levels induced by LPS.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding PRL secretion, α-MSH blocks IL-1-stimulated PRL release [24]whereas AgRP stimulates PRL release in the monkey [39]supporting the idea of a physiological role for endogenous α-MSH in PRL secretion. α-MSH has been shown to suppress, whereas an α-MSH antiserum has been shown to enhance, basal and stress-induced PRL secretion [42].…”
Section: Discussionmentioning
confidence: 95%
“…We propose that the blunted fasting-induced CRH response results from a blunted NPY and AgRP response. Intracerebroventricular injection of either AgRP or NPY ICV has been shown to increase corticosterone (21,22). Surprisingly, the MC3/4-R agonist MTII also increases circulating corticosterone (53).…”
Section: Discussionmentioning
confidence: 97%
“…Because neuropeptide Y (NPY) and AgRP peptides play a role in the fasting-induced increase in CRH mRNA (21,22), and that the MC3-R −/− mouse displayed a defect in fasting-induced CRH mRNA expression, fasting-induced refeeding and fasting-induced changes in NPY and AgRP mRNA expression were characterized in the MC3-R −/− mouse. Fasting-induced 12-h refeeding was blunted in MC3-R −/− mice (Fig.…”
Section: Mc3-r −/− Mice Exhibit Elevated Basal Corticosterone and Defmentioning
confidence: 99%
“…All of the finely integrated key components and upstream regulators of the melanocortin system have widespread immunologic influence modulated via their downstream targets [Xiao et al, 2003;La Cava and Matarese, 2004;Matarese and La Cava, 2004;Taub, 2008;Savos et al, 2011] and some also act as neuroimmune cotransmitters [Bedoui et al, 2003]. Cytokines are the effector molecule links between immune response and the neuroendocrine system.…”
mentioning
confidence: 99%